2022
DOI: 10.1021/acsami.2c19531
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and Photoelectrochemical Detection of Hydrogen Peroxide Using Cu2O/Cu Nanowires Decorated with TiO2−x Deriving from MXenes

Abstract: H 2 O 2 is a major transmitter of redox signals in electrochemical processes, whose detection is relevant for various industries. Herein, we developed a new fabrication method for a Cu 2 O/Cu nanowire-based nonenzymatic H 2 O 2 electrochemical sensor that was decorated with irregular TiO 2−x nanoparticles deriving form Ti 3 C 2 MXene. The TiO 2−x /Cu 2 O/Cu-NW electrodes possess excellent selectivity, stability, and reproducibility for H 2 O 2 detection in both EC and PEC operational modes. In the EC detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 44 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…41 However, the presence of Ti 3 C 2 QDs can be confirmed from the HRTEM image of Ti 3 C 2 QDs/Cu NWs as shown in Fig. 1D, which shows the distance of the lattice fringes to be 0.26 nm 42 corresponding to the Ti 3 C 2 QDs (0110) plane, and a distance of 0.198 nm 43 corresponding to the Cu (111) plane. The SEM image of Ti 3 C 2 QDs/Cu NWs shown in Fig.…”
Section: Resultsmentioning
confidence: 81%
“…41 However, the presence of Ti 3 C 2 QDs can be confirmed from the HRTEM image of Ti 3 C 2 QDs/Cu NWs as shown in Fig. 1D, which shows the distance of the lattice fringes to be 0.26 nm 42 corresponding to the Ti 3 C 2 QDs (0110) plane, and a distance of 0.198 nm 43 corresponding to the Cu (111) plane. The SEM image of Ti 3 C 2 QDs/Cu NWs shown in Fig.…”
Section: Resultsmentioning
confidence: 81%
“…Herein, several anti-interference substances were selected based on the consideration of components in real body blood, including NaCl, uric acid (UA), dopamine (DA), ascorbic acid (AA), and lactic acid. In order to maintain consistency with previous reports, the concentration ratio of H 2 O 2 and interferents with 10:1 was adopted for the anti-interference test. Herein, 50 μM H 2 O 2 , 5 μM NaCl, 5 μM UA, 5 μM lactate, 5 μM AA, and 5 μM DA were added sequentially to a 0.1 M NaOH solution at 0.65 V. As illustrated in Figure c that there was a significant current response with the addition of H 2 O 2 , yet the negligible current response to NaCl, UA, lactic acid, AA, and DA, which indicated that PBA/UiO-66/NF had excellent selectivity to H 2 O 2 . Similarly, the reproducibility of the PBA/UiO-66/NF electrode was also assessed.…”
Section: Resultsmentioning
confidence: 85%
“…Trace level detection of H 2 O 2 is crucial in the food industry, life science, domestic settings, etc. , Because H 2 O 2 is readily converted to strong oxidizing species, such as hydroxyl free radicals ( • OH), superoxide radical (O 2 – •), singlet oxygen, etc., which may promote the aging of the cell, induce the oxidation of lipids and proteins, damage the structure of the DNA, and so on. Although various techniques have so far been developed to identify and monitor H 2 O 2 , including colorimetric analysis, , fluorescence analysis, , electrochemical analysis, , etc., the cost, stability, and sensitivity obtained by these tactics are poor and lower minimum detection limit of H 2 O 2 is relatively high . Therefore, seeking suitable strategies to achieve the cost efficiency and detection accuracy of trace H 2 O 2 is of tremendous urgency but is a great challenge in the modern chemical industry.…”
Section: Introductionmentioning
confidence: 99%